Analisis Peran Konsultan Pajak Dalam Meningkatkan Kepatuhan Wajib Pajak Badan di KPP Pratama Telanaipura Jambi tahun 2022 - Theresia, Maya; Irawan, Bambang (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research focuses on analyzing the role of consultants in improving taxpayer compliance at KPP Pratama Telanaipura Jambi in 2022. This research aims to understand how tax consultants contribute to enhancing taxpayer compliance and identify the challenges and efforts faced by tax consultants in improving taxpayer compliance. The research utilizes a qualitative descriptive method, employing data collection techniques such as observation, interviews, and document analysis. The findings reveal that tax consultants can influence taxpayer compliance by providing sound advice and solutions to their clients. Challenges faced by tax consultants include encountering taxpayers unwilling to pay after determining their tax liabilities and taxpayers lacking understanding of tax regulations. Efforts made by tax consultants involve staying updated on prevailing tax regulations.